Sosialisasi Pentingnya Pendampingan Orang Tua dalam Proses Belajar Membaca Siswa Kelas 1 SD di Desa Karanggintung - Sigit Andi Prasetya Dinata; Lutfi Eskawati; Winda Warohmah (Jurnal Pengabdian Masyarakat Nusantara, 2021)
This article dsiscusses the importance of parental assistance in the process of learning to read for grade 1 students at SD KARANGUNTUNG VILLAGE. Parental involvement at home plays a very important role in building a strong early literacy foundation for children. Through effective assistance, students will more easily understand reading learning material, improve their literacy skills, and increase their confidence in communicating. This research aims to understand the role of parents in supporting children's learning to read at home and to provide practical recommendations for parents in carrying out this role. The methods used in this article are literature studies and field observations which provide a real picture of the positive impact of parental assistance